PERAN SIKAP DALAM MEMEDIASI PENGARUH ECOLITERACY TERHADAP KESEDIAAN UNTUK MEMBELI PRODUK RAMAH LINGKUNGAN - Suwondo, Septika Permana Dewi; Pramudana, Km. Agus Satria (E-Jurnal Manajemen, 2016)
Community knowledge of the environment is still lacking, judging by the cleanliness of the environment that is in the nearby community still needs to be improved. Concern for the environment has made increasing demand for environmentally friendly products. This has created a new environmental ethic, and has increased awareness of individuals significantly alter consumption behavior. This study aims to determine whether attitudes play a role in mediating the effects of Ecoliteracy the willingness to buy environmentally friendly products. Samples were determined by non-probability sampling technique with the respondent. The sample size used in this study were 103 respondents using path analysis techniques. The results of this study indicate that (1) Ecoliteracy positive and significant impact on consumer attitudes, (2) Ecoliteracy positive and significant effect on the willingness to buy environmentally friendly products, (3) Attitude positive and not significant to the willingness to buy environmentally friendly products, (4) mediation variables that attitude assessed the significance of mediating the relationship between Ecoliteracy the willingness to buy environmentally friendly products.
Keywords: Ecoliteracy, Attitudes, Willingness To Buying Environmentally Friendly Products